An invitation to social construction - Gergen, Kenneth J. (Los Angeles Sage, 2015)
In 'An Invitation to Social Construction', Kenneth Gergen charts the background to the social constructionist movement and outlines the major debates, topics and issues.
Includes bibliographical references (pages [235]-247) and index.
Keywords: Social psychology; Social problems; Discourse analysis; Subjectivity; Social interaction